Engaging children as "agents of change": The Grahamstown Scout Group - Saneka, Nora E. (HTS teologiese studies, 2019)
This article, as a narrative, offers a ‘learning journey’ of the Grahamstown Scout Group, and reveals how ‘the child’s right to participation’ (United Nations Convention on the Rights of the Child, UNCRC 1989) is actualised in the life and workings of this group. The methodology used by the facilitator of the Scout Group explores different ways of listening and responding to the children, inspired by three different approaches on working with children that overlap and resonate with each other. The article outlines various ways in which the ‘image’ of the child is a historical and social interpretation and explores the meaning of this for theology and children’s ministry. A ‘rights-based approach’ to working with children reveals them as created in the ‘image of God’ and co-constructors with God of a ‘better world for children’, as they become ‘agents of change’.